DEVELOPMENT OF A PROJECT-BASED LEARNING MODULE FOR INDONESIAN CAKE AND PASTRY PRODUCTS TO IMPROVE CREATIVITY AND CRITICAL THINKING SKILLS OF WIRA HARAPAN VOCATIONAL SCHOOL STUDENTS: Pengembangan Modul Pembelajaran Produk Cake dan Kue Indonesia Berbasis Proyek untuk Meningkatkan Kreativitas dan Kemampuan Berpikir Kritis Siswa SMK Wira Harapan - I Putu Pranatha Sentosa; Ni Made Erpia Ordani Astuti; Vinsensa Yuniarti Harmin; I Kadek Edo Purnawan; I Gusti Ayu Ika Monika Prastyandhari (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The purpose of this research is to produce a project-based learning module of Indonesian Cake and Cake Products (PCKI) in accordance with the Vocational High School (SMK) curriculum that is valid, practical and effective to improve students' critical thinking skills in learning Indonesian cake and cake products (PCKI). This research uses Development (R&D), to produce new products or improve existing products using the ADDIE Development model. The research subjects were one content expert and a linguist for the validity test, one teacher and 6 students for the practicality test and the study group for the effectiveness test. The instruments used in this study are content and language validity tests, practicality test instruments, and effectiveness test instruments in the form of tests to increase students' creativity and critical thinking. The data collection techniques used are through observation, interviews, questionnaires, tests and documentation. Overall, the Aiken index showed a score of 0.897 in the